Iron aggravates hepatic insulin resistance in the absence of inflammation in a novel db/db mouse model with iron overload - Sandro Altamura; Katja Müdder; Andrea Schlotterer; Thomas Fleming; Elena Heidenreich; Ruiyue Qiu; Hans-Peter Hammes; Peter Nawroth; Martina U. Muckenthaler (Elsevier, 2021)
Objective: The molecular pathogenesis of late complications associated with type 2 diabetes mellitus (T2DM) is not yet fully understood. While high glucose levels indicated by increased HbA1c only poorly explain disease progression and late complications, a pro-inflammatory status, oxidative stress, and reactive metabolites generated by metabolic processes were postulated to be involved. Individuals with metabolic syndrome (MetS) frequently progress to T2DM, whereby 70% of patients with T2DM show non-alcoholic fatty liver disease (NAFLD), the hepatic manifestation of MetS, and insulin resistance (IR). Epidemiological studies have shown that T2DM and steatosis are associated with alterations in iron metabolism and hepatic iron accumulation. Excess free iron triggers oxidative stress and a switch towards a macrophage pro-inflammatory status. However, so far it remains unclear whether hepatic iron accumulation plays a causative role in the generation of IR and T2DM or whether it is merely a manifestation of altered hepatic metabolism. To address this open question, we generated and characterized a mouse model of T2DM with IR, steatosis, and iron overload. Methods: Leprdb/db mice hallmarked by T2DM, IR and steatosis were crossed with Fpnwt/C326S mice with systemic iron overload to generate Leprdb/db/Fpnwt/C326S mice. The resulting progeny was characterized for major diabetic and iron-related parameters. Results: We demonstrated that features associated with T2DM in Leprdb/db mice, such as obesity, steatosis, or IR, reduce the degree of tissue iron overload in Fpnwt/C326S mice, suggesting an 'iron resistance' phenotype. Conversely, we observed increased serum iron levels that strongly exceeded those in the iron-overloaded Fpnwt/C326S mice. Increased hepatic iron levels induced oxidative stress and lipid peroxidation and aggravated IR, as indicated by diminished IRS1 phosphorylation and AKT activation. Additionally, in the liver, we observed gene response patterns indicative of de novo lipogenesis and increased gluconeogenesis as well as elevated free glucose levels. Finally, we showed that iron overload in Leprdb/db/Fpnwt/C326S mice enhances microvascular complications observed in retinopathy, suggesting that iron accumulation can enhance diabetic late complications associated with the liver and the eye. Conclusion: Taken together, our data show that iron causes the worsening of symptoms associated with the MetS and T2DM. These findings imply that iron depletion strategies together with anti-diabetic drugs may ameliorate IR and diabetic late complications.